2012
DOI: 10.1111/j.1540-8175.2012.01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Noncompaction of Right Ventricle—A Case Report

Abstract: Isolated noncompaction of ventricular myocardium (INVM) is a genetic cardiomyopathy due to abnormal arrest in endomyocardial embryogenesis between fetal 5th and 8th week. Noncompaction of right ventricle alone is rare. Here we present one such case where a young man presented with progressive right heart failure and atrial fibrillation. Subsequent evaluation by echo and cardiac magnetic resonance imaging confirmed our diagnosis. The cardinal manifestations of INVM are heart failure, arrhythmia, and embolic eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
0
16
0
3
Order By: Relevance
“…[5] RV NC can exist in combination with LV NC[6] or in isolation. [7] The association between RV NC and atrial septal defect has been previously reported;[8] however, the present study presents the first case of an association with atrial septal defect (sinus venosus type) and partial anomalous connection of the right upper pulmonary vein.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…[5] RV NC can exist in combination with LV NC[6] or in isolation. [7] The association between RV NC and atrial septal defect has been previously reported;[8] however, the present study presents the first case of an association with atrial septal defect (sinus venosus type) and partial anomalous connection of the right upper pulmonary vein.…”
Section: Discussionmentioning
confidence: 63%
“…[8] Preoperative RV dysfunction in this case can be due to volume overload or in association with NC. [78]…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular noncompaction, is a rare cardiomyopathy reported 28 years ago by Engberding and Benber in a 33‐year‐old female patient and by Chin et al. as an isolated lesion in 22 years ago . Occurrence of ALVT associated with noncompaction and RCA arising from the tunnel is exceedingly rare.…”
Section: Discussionmentioning
confidence: 95%
“…LVNC, a genetic form of cardiomyopathy, has been well described in patients with and without associated congenital heart disease . However, RVNC as an isolated disease has been reported in children only in isolated case reports . Even fewer case reports have been published demonstrating RVNC in congenital heart disease, and has been limited to two‐ventricle heart disease .…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, RVNC as an isolated disease has been reported in children only in isolated case reports. [8][9][10] Even fewer case reports have been published demonstrating RVNC in congenital heart disease, and has been limited to two-ventricle heart disease. 11 To our knowledge, this case series is the first to describe RVNC in HLHS.…”
Section: Discussionmentioning
confidence: 99%